Extension-Market Linkages on Banana Commercialisation Among Smallholder Farmers in Meru Region, Kenya - Kirimi, Florence Kaumi; Onyari, Charles Nyambane; Njeru, Lucy Karega; Mogaka, Hezron Rasugu (Journal of Agricultural Extension, 2022)
The study examined the effect of extension-market linkages on banana commercialisation among smallholder farmers in the Meru region, Kenya. The study sampled 400 farmers from a target population of 288,802 from the Meru region. The Tobit model was used to analyse the effect of extension-market linkages on banana commercialisation. The results revealed that sources of marketing information (Coef. -0.06) had a negative influence on farmers commercialising banana production. The result showed that the reliability of local extension service providers in enabling farmer’s access to market information (Coef. 0.04) had a positive influence on farmers commercialising banana production. The findings also showed that users of marketing information in the commercialisation banana business (Coef. 0.63) had a positive influence on farmers commercialising banana production. The study concludes that there was an association between extension marketing linkages and banana commercialization among smallholder farmers in Meru region, Kenya. Government should create and implement more policies that will favour and encourage farmers to commercialise bananas. This will help farmers increase their income.
Article
Keywords: Extension-market linkages; banana commercialisation; smallholder farmers.